Science Laboratory Environment and Students’ Motivation as Predictors on Attitudes Towards Physics Lesson - Nadrah Nadrah (Jurnal Penelitian Pendidikan IPA, 2025)
Physics learning plays a significant role in shaping students’ attitudes towards science subjects, especially Physics. In addition, students’ motivation level significantly influences their engagement and performance in this subject. This study investigated the combined effect of Science Laboratory Environment and students’ motivation as predictors of students’ attitudes towards Physics. This study aimed to determine the significant combined effect of science laboratory environment and students’ motivation on students’ attitudes towards Physics. This study used a non-experimental quantitative method using descriptive, correlational, and predictive approaches. In addition, the respondents of this study were selected through purposive sampling of 100 junior high school students from private schools in Davao City and answered 3 survey questionnaires adopted. Using Mean and Pearson r, the findings showed the following; science laboratory environment is high while students’ motivation and students’ attitudes towards Physics. Furthermore, combining the two predictor variables science laboratory environment and students’ motivation showed a significant effect on students’ attitudes towards Physics.